A concise review of chewing gum as an anti-cariogenic agent - Yeung, Clara Yan-Yu; Chu, Chun-Hung; Yu, Ollie Yiru (Frontiers in Oral Health, 2023)
Chewing gum has been endorsed as a caries preventive agent by the FDI World Dental Federation, the American Dental Association, and the European Food Safety Authority. This review discusses the mechanism and provides an update of the use of chewing gum for caries prevention. Chewing gum typically consists of a water-insoluble gum base, water-soluble added ingredients, and active ingredients. It can be classified as sugar-containing or sugar-free, as well as nonmedicated or medicated. Chewing gum prevents dental caries through a range of mechanisms, including the clearance of the oral cavity, neutralization of oral acidity, inhibition of cariogenic bacterial growth, remineralization of enamel, and reduction of appetite. Recent clinical studies have evaluated the efficacy of sugar-free chewing gum for caries prevention, with most demonstrating positive results, although some studies have reported contradictory outcomes. To achieve optimal caries prevention, it is generally recommended that individuals chew sugar-free gum for five minutes after meals, three times daily.